Differences in Students’ Computational Thinking Activities when Designing an Algorithm for Drawing Plane Figures: Differences in students’ Computational Thinking Activities when Designing an Algorithm for Drawing Plane Figures - Büscher, Carina (International journal of science and mathematics education, 2025)
Computational thinking (CT) is becoming increasingly important as a learning content. Subject-integrated approaches aim to develop CT within other subjects like mathematics. The question is how exactly CT can be integrated and learned in mathematics classrooms. In a case study involving 12 sixth-grade learners, CT activities were explored that learners engage in when drawing geometric figures with a visual programming language. The empirical findings indicate differences not only across various CT activities but also within a single CT activity. Subcategories were developed to describe these differences. Implications for further research and classroom practice are discussed.